Comparison of the Effectiveness of Spiritual Therapy and Supportive Psychotherapy on Coping Styles and Subjective Health Complaints in Patients with Metabolic Syndrome - Ansari Shahidi, Morteza; Jabalameli, Sheida; Ansari Shahidi , Mojtaba; Sobhani , Ahmad; Mousavizadeh, Seyed Rouhollah (Mental Health and Lifestyle Journal, 2026)
The present study aimed to compare the effectiveness of spiritual therapy and supportive psychotherapy on coping styles and subjective health complaints in patients with metabolic syndrome. This study was conducted using a quasi-experimental design with pretest–posttest and follow-up phases. The research population consisted of patients with metabolic syndrome who attended healthcare centers in Tehran in 2025. A total of 45 eligible patients were randomly assigned to three groups: spiritual therapy, supportive psychotherapy, and control. Research instruments included the Ursin Subjective Health Complaints Questionnaire and the Lazarus Coping Strategies Questionnaire. The spiritual therapy group received the multidimensional Godaso spiritual treatment package (12 sessions), the supportive psychotherapy group received 10 sessions of supportive therapy, and the control group received no intervention. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests. The results indicated that both therapeutic approaches significantly improved coping styles and reduced subjective health complaints (p < .001). Spiritual therapy demonstrated greater effectiveness in enhancing problem-focused coping and reducing emotion-focused coping, whereas supportive psychotherapy showed relative superiority in reducing subjective health complaints compared to spiritual therapy. These effects remained stable during the follow-up phase. The findings highlight the importance of multidimensional, culturally grounded psychological interventions in improving psychological and physical outcomes in patients with metabolic syndrome. The results also indicate that spiritual therapy and supportive psychotherapy may complement each other in managing these patients.